Polarizing film with adhesive layer, polarizing film with adhesive layer for embedded liquid crystal panel, embedded liquid crystal panel, and liquid crystal display device

By using a polarizing film with a conductive polymer sticking layer and an antistatic adhesive layer in the embedded liquid crystal cell of the liquid crystal display device, the problems of static electricity generation and malfunction of the touch sensor are solved, and a stable antistatic function and a high-sensitivity touch sensor are realized.

CN119620277APending Publication Date: 2025-03-14NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411583109.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-03-28
Filing Date
2018-03-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, it is difficult to effectively suppress the generation of static electricity and the malfunction of the touch sensor in a liquid crystal display device. Especially in an embedded liquid crystal cell, the improper arrangement position of the antistatic layer and the small contact area of ​​the conducting structure lead to uneven static electricity and the reduction of the touch sensor sensitivity.

Method used

A polarizing film with a conductive polymer adhesive layer and an antistatic agent adhesive layer is adopted. By controlling the thickness and surface resistance of each layer, the conductive structure and the adhesive layer are ensured to have a good contact between the conductive structure and the adhesive layer, and a stable antistatic function and a high sensitivity touch sensor are achieved.

Benefits of technology

It effectively suppresses the generation of static electricity and unevenness of static electricity, improves the sensitivity of the touch sensor, avoids the occurrence of malfunctions, and maintains the anti-static function and the stability of the adhesive layer in a humidified environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119620277A_ABST
    Figure CN119620277A_ABST
Patent Text Reader

Abstract

The present invention provides a polarizing film with an adhesive layer, which is used for realizing an in-cell liquid crystal panel having excellent adhesion between a tackifier layer and an adhesive layer and satisfying a stable antistatic function and sensitivity of a touch sensor. The polarizing film with the adhesive layer comprises an adhesive layer and a polarizing film, the polarizing film with the adhesive layer comprises the polarizing film, a tackifying layer and the adhesive layer in the stated order, the tackifying layer contains a conductive polymer, the adhesive layer contains an antistatic agent, the thickness of the tackifying layer is 0.01-0.5 [mu] m, the surface resistance value is 1.0 * 10 < 8 >-1.0 * 10 < 10 > Omega / square, and the thickness of the tackifying layer is 0.01-0.5 [mu] m and the surface resistance value is 1.0 * 10 < 8 >-1.0 * 10 < 10 > Omega / square. The thickness of the adhesive layer is 5-100 [mu] m, the surface resistance value is 1.0 * 1010-1.0 * 1012 [omega] / square, and the variation ratio (b / a) of the surface resistance value before and after humidification on the adhesive layer side is 5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application with application date of March 28, 2018, application number of 201880021947.7, and invention name of “Polarizing film with adhesive layer, polarizing film with adhesive layer for built-in liquid crystal panel, built-in liquid crystal panel and liquid crystal display device”. Technical Field

[0002] The present invention relates to a polarizing film with an adhesive layer, a polarizing film with an adhesive layer for an in-cell liquid crystal panel, an in-cell liquid crystal cell with a touch sensing function introduced inside the liquid crystal cell, and an in-cell liquid crystal panel having a polarizing film with an adhesive layer on the visible side of the in-cell liquid crystal cell. In addition, the present invention also relates to a liquid crystal display device using the above liquid crystal panel. The liquid crystal display device with a touch sensing function using an in-cell liquid crystal panel of the present invention can be used as various input display devices such as mobile devices. Background Art

[0003] Liquid crystal display devices are usually laminated with polarizing films from both sides of the liquid crystal unit through adhesive layers according to their image formation method. In addition, products that mount touch panels on the display screen of liquid crystal display devices have also been put into practical use. As touch panels, there are various methods such as capacitive, resistive film, optical, ultrasonic or electromagnetic induction, but capacitive is beginning to be widely used. In recent years, liquid crystal display devices with touch sensing functions that have built-in capacitive sensors as touch sensor parts have been used.

[0004] On the other hand, when manufacturing a liquid crystal display device, when the polarizing film with an adhesive layer is attached to the liquid crystal unit, the release film is peeled off from the adhesive layer of the polarizing film with an adhesive layer, but static electricity is generated due to the peeling of the release film. In addition, static electricity is also generated when the surface protective film of the polarizing film attached to the liquid crystal unit is peeled off and when the surface protective film of the cover window is peeled off. The static electricity generated in this way affects the orientation of the liquid crystal layer inside the liquid crystal display device, resulting in defects. The generation of static electricity can be suppressed by, for example, forming an antistatic layer on the outer surface of the polarizing film.

[0005] On the other hand, the capacitive sensor in a liquid crystal display device with a touch sensing function detects the weak capacitance formed between the transparent electrode pattern and the finger when the user's finger approaches the surface. When there is a conductive layer such as an antistatic layer between the transparent electrode pattern and the user's finger, the electric field between the drive electrode and the sensor electrode is disturbed, the sensor electrode capacitance becomes unstable, and the sensitivity of the touch panel is reduced, which becomes a cause of malfunction. In a liquid crystal display device with a touch sensing function, it is required to suppress the malfunction of the capacitive sensor while suppressing the generation of static electricity. For example, in order to reduce the occurrence of poor display and malfunction in a liquid crystal display device with a touch sensing function, it is proposed to configure a liquid crystal layer with a surface resistance of 1.0×10 9 ~1.0×10 11 A polarizing film having an antistatic layer of Ω / □ (Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-105154 Summary of the invention

[0009] Problems to be solved by the invention

[0010] According to the polarizing film with an antistatic layer described in Patent Document 1, it is possible to suppress the generation of static electricity to a certain extent. However, in Patent Document 1, since the configuration position of the antistatic layer deviates from the position of the liquid crystal unit that has poor display due to static electricity, it is not effective compared to the case where the antistatic function is given to the adhesive layer. In addition, it is known that the embedded liquid crystal unit is more easily charged than the so-called on-cell liquid crystal unit having a sensor electrode on the transparent substrate of the liquid crystal unit described in Patent Document 1. In addition, it is known that for a liquid crystal display device with a touch sensing function using an embedded liquid crystal unit, conductivity can be given from the side by providing a conductive structure on the side of the polarizing film, but in the case of a thin antistatic layer, since the contact area between the side and the conductive structure is small, sufficient conductivity cannot be obtained, resulting in poor conductivity. On the other hand, it is known that when the antistatic layer is thickened, the sensitivity of the touch sensor decreases.

[0011] On the other hand, the adhesive layer endowed with an antistatic function is more effective than the antistatic layer provided on the above-mentioned polarizing film in suppressing the generation of static electricity and preventing uneven static electricity. However, it is known that when the antistatic function of the adhesive layer is emphasized and the conductive function of the adhesive layer is improved, the sensitivity of the touch sensor is reduced. In particular, it is known that for a liquid crystal display device with a touch sensing function using an embedded liquid crystal unit, the sensitivity of the touch sensor is reduced. It is also known that the antistatic agent added to the adhesive layer in order to improve the conductive function will segregate at the interface with the polarizing film in a humidified environment (after a humidified reliability test), causing the adhesive layer to become turbid.

[0012] The object of the present invention is to provide a polarizing film with an adhesive layer, an embedded liquid crystal unit, and a polarizing film with an adhesive layer for an embedded liquid crystal panel suitable for its visible side, and the embedded liquid crystal panel having the polarizing film with an adhesive layer, wherein the adhesion between the tackifying layer and the adhesive layer of the embedded liquid crystal panel is excellent, and the stable antistatic function and touch sensor sensitivity can be satisfied. In addition, the object of the present invention is to provide a liquid crystal display device using the embedded liquid crystal panel.

[0013] Solutions to the problem

[0014] The present inventors have repeatedly conducted intensive studies to solve the above problems and have found that the above problems can be solved by the following polarizing film with an adhesive layer, polarizing film with an adhesive layer for an embedded liquid crystal panel, and embedded liquid crystal panel, thereby completing the present invention.

[0015] That is, the pressure-sensitive adhesive layer-attached polarizing film of the present invention comprises a pressure-sensitive adhesive layer and a polarizing film.

[0016] The polarizing film with an adhesive layer comprises the polarizing film, an adhesion-promoting layer, and the adhesive layer in this order.

[0017] The adhesion-promoting layer contains a conductive polymer, and the adhesive layer contains an antistatic agent.

[0018] The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □,

[0019] The thickness of the adhesive layer is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, and

[0020] The variation ratio (b / a) of the surface resistance value on the adhesive layer side is 5 or less,

[0021] Among them, the above-mentioned a represents the surface resistance value of the adhesive layer side when the above-mentioned diaphragm is peeled off immediately after the polarizing film with an adhesive layer is produced in a state in which the above-mentioned adhesive layer is provided on the above-mentioned polarizing film and the diaphragm is provided on the above-mentioned adhesive layer; the above-mentioned b represents the surface resistance value of the adhesive layer side when the above-mentioned diaphragm is peeled off after the above-mentioned polarizing film with an adhesive layer is placed in a humidified environment of 60℃×95%RH for 120 hours and further dried at 40℃ for 1 hour.

[0022] In the pressure-sensitive adhesive layer-attached polarizing film of the present invention, the antistatic agent is preferably an ionic compound having an inorganic cation.

[0023] In the pressure-sensitive adhesive layer-attached polarizing film of the present invention, the ionic compound preferably contains a fluorine-containing anion.

[0024] In addition, the polarizing film with an adhesive layer for an embedded liquid crystal panel of the present invention is used for an embedded liquid crystal panel having an embedded liquid crystal unit, wherein the embedded liquid crystal unit has: a liquid crystal layer including liquid crystal molecules uniformly oriented in the absence of an electric field, a first transparent substrate and a second transparent substrate sandwiching the liquid crystal layer on both sides, and a touch sensing electrode portion related to a touch sensor and a touch driving function between the first transparent substrate and the second transparent substrate.

[0025] The polarizing film with the adhesive layer is disposed on the visible side of the built-in liquid crystal unit.

[0026] The adhesive layer of the polarizing film with an adhesive layer is disposed between the polarizing film of the polarizing film with an adhesive layer and the in-cell liquid crystal cell.

[0027] The polarizing film with an adhesive layer comprises the polarizing film, an adhesion-promoting layer, and the adhesive layer in this order.

[0028] The adhesion-promoting layer contains a conductive polymer, and the adhesive layer contains an antistatic agent.

[0029] The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □,

[0030] The thickness of the adhesive layer is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, and

[0031] The variation ratio (b / a) of the surface resistance value on the adhesive layer side is 5 or less,

[0032] Among them, the above-mentioned a represents the surface resistance value of the adhesive layer side when the above-mentioned diaphragm is peeled off immediately after the polarizing film with an adhesive layer is produced in a state in which the above-mentioned adhesive layer is provided on the above-mentioned polarizing film and the diaphragm is provided on the above-mentioned adhesive layer; the above-mentioned b represents the surface resistance value of the adhesive layer side when the above-mentioned diaphragm is peeled off after the above-mentioned polarizing film with an adhesive layer is placed in a humidified environment of 60℃×95%RH for 120 hours and further dried at 40℃ for 1 hour.

[0033] In the pressure-sensitive adhesive layer-attached polarizing film for an in-cell type liquid crystal panel of the present invention, the antistatic agent is preferably an ionic compound having an inorganic cation.

[0034] In the pressure-sensitive adhesive layer-attached polarizing film for an in-cell type liquid crystal panel of the present invention, the ionic compound preferably contains a fluorine-containing anion.

[0035] The in-cell liquid crystal panel of the present invention comprises an in-cell liquid crystal cell and a polarizing film with an adhesive layer disposed on a first transparent substrate on a visible side of the in-cell liquid crystal cell via a first adhesive layer.

[0036] The embedded liquid crystal unit comprises: a liquid crystal layer including liquid crystal molecules uniformly oriented in the absence of an electric field, a first transparent substrate and a second transparent substrate sandwiching the liquid crystal layer on both sides, and a touch sensing electrode portion related to touch sensor and touch driving functions between the first transparent substrate and the second transparent substrate.

[0037] The polarizing film with an adhesive layer comprises the first polarizing film, an adhesion-promoting layer, and the first adhesive layer in this order.

[0038] The above-mentioned adhesion-promoting layer contains a conductive polymer, and the above-mentioned first adhesive layer contains an antistatic agent.

[0039] The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □,

[0040] The thickness of the first adhesive layer is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, and

[0041] The variation ratio (b / a) of the surface resistance value on the first adhesive layer side is 5 or less,

[0042] Among them, the above-mentioned a represents the surface resistance value of the first adhesive layer side when the above-mentioned diaphragm is immediately peeled off after the first polarizing film with an adhesive layer is produced in a state in which the above-mentioned first adhesive layer is provided on the above-mentioned first polarizing film and a diaphragm is provided on the above-mentioned first adhesive layer; the above-mentioned b represents the surface resistance value of the first adhesive layer side when the above-mentioned diaphragm is peeled off after the above-mentioned first polarizing film with an adhesive layer is placed in a humidified environment of 60℃×95%RH for 120 hours and further dried at 40℃ for 1 hour.

[0043] In the in-cell liquid crystal panel of the present invention, it is preferable that the antistatic agent is an ionic compound having an inorganic cation.

[0044] In the in-cell liquid crystal panel of the present invention, it is preferred that the ionic compound contains a fluorine-containing anion.

[0045] Furthermore, it is preferable that the liquid crystal display device of the present invention includes the above-mentioned in-cell liquid crystal panel.

[0046] Effects of the Invention

[0047] The polarizing film with adhesive layer on the visible side of the embedded liquid crystal panel of the present invention contains a conductive polymer in the adhesion layer and an antistatic agent in the adhesive layer, thereby imparting an antistatic function. Therefore, in the embedded liquid crystal panel, when a conductive structure is provided on each side of the adhesion layer and the adhesive layer, the conductive structure can be contacted, and the adhesion layer and the adhesive layer have a given thickness range, respectively, so that the contact area can be fully ensured. Therefore, the conduction on the side of each layer of the adhesion layer and the adhesive layer can be ensured, thereby suppressing the occurrence of static unevenness caused by poor conduction.

[0048] In addition, the polarizing film with an adhesive layer of the present invention controls the surface resistance values ​​of the adhesion layer and each layer of the adhesive layer to a given range, and controls the change ratio of the surface resistance value before and after humidification of the above-mentioned (first) adhesive layer side to a given range, so that the surface resistance values ​​of the adhesion layer and the adhesive layer can be reduced without reducing the sensitivity of the touch sensor, thereby imparting a given antistatic function. In addition, by controlling the surface resistance value of the adhesive layer to a given range, antistatic properties can be obtained while suppressing the amount of antistatic agent used, and turbidity can be suppressed, which is useful. Therefore, the polarizing film with an adhesive layer of the present invention can meet the sensitivity of the touch sensor while having a good antistatic function. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a cross-sectional view showing an example of a polarizing film with a pressure-sensitive adhesive layer used on the viewing side of the in-cell type liquid crystal panel of the present invention.

[0050] Figure 2This is a cross-sectional view showing an example of the in-cell type liquid crystal panel of the present invention.

[0051] Figure 3 This is a cross-sectional view showing an example of the in-cell type liquid crystal panel of the present invention.

[0052] Figure 4 This is a cross-sectional view showing an example of the in-cell type liquid crystal panel of the present invention.

[0053] Figure 5 This is a cross-sectional view showing an example of the in-cell type liquid crystal panel of the present invention.

[0054] Figure 6 This is a cross-sectional view showing an example of the in-cell type liquid crystal panel of the present invention.

[0055] Explanation of symbols

[0056] A Polarizing film with adhesive layer

[0057] B In-cell liquid crystal unit

[0058] C In-cell LCD panel

[0059] 1, 11 1st and 2nd polarizing films

[0060] 2, 12 1st and 2nd adhesive layers

[0061] 3 Adhesion layer

[0062] 4 Surface treatment layer

[0063] 20 Liquid crystal layer

[0064] 31 Touch sensor electrodes

[0065] 32 touch drive electrodes

[0066] 33 Touch drive electrode and sensor electrode

[0067] 41, 42 1st, 2nd transparent substrate DETAILED DESCRIPTION

[0068] <Polarizing Film with Adhesive Layer>

[0069] Hereinafter, the present invention will be described with reference to the accompanying drawings. Figure 1 As shown, the polarizing film A with adhesive layer used on the visible side of the in-cell liquid crystal panel of the present invention sequentially comprises a first polarizing film 1, an adhesion layer 3, and a first adhesive layer 2. In addition, a surface treatment layer 4 may be provided on the side of the first polarizing film 1 where the adhesion layer 3 is not provided. Figure 1 The example in the figure shows the case where the pressure-sensitive adhesive layer-attached polarizing film A of the present invention has a surface-treated layer 4. Figure 2The transparent substrate 41 side of the visible side of the embedded liquid crystal unit B1 shown in FIG. Figure 1 Although not described in the specification, the first pressure-sensitive adhesive layer 2 of the pressure-sensitive adhesive layer-attached polarizing film A of the present invention may be provided with a separator, and the first polarizing film 1 may be provided with a surface protective film.

[0070] <First Polarizing Film>

[0071] As the first polarizing film, a film having a transparent protective film on one or both sides of a polarizer is generally used.

[0072] The polarizer is not particularly limited, and various polarizers can be used. Examples of the polarizer include: polarizers obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers, and then uniaxially stretching them; polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. Among them, polarizers containing dichroic substances such as polyvinyl alcohol films and iodine are preferred. There is no particular limitation on the thickness of these polarizers, but it is generally about 80 μm or less.

[0073] In addition, as a polarizer, a thin polarizer with a thickness of 10 μm or less can be used. From the viewpoint of thinning, the thickness is preferably 1 to 7 μm. Such a thin polarizer has less uneven thickness, excellent visibility, and less dimensional change, so it has excellent durability, and the thickness of the polarizing film can also be thinned, which is preferred in this respect.

[0074] As the material constituting the transparent protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include, for example, cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. It should be noted that a transparent protective film can be attached to one side of the polarizer through an adhesive layer, and a thermosetting resin or ultraviolet curing resin such as (meth) acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. can be used as a transparent protective film on the other side. The transparent protective film can contain one or more of any appropriate additives.

[0075] The adhesive used in laminating the polarizer and the transparent protective film is not particularly limited as long as it is optically transparent. Various forms of adhesives such as aqueous, solvent-based, hot melt, free radical curing, and cation curing can be used, preferably aqueous adhesives or free radical curing adhesives.

[0076] <First Adhesive Layer>

[0077] The thickness of the first adhesive layer constituting the in-cell liquid crystal panel of the present invention is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, the first adhesive layer contains an antistatic agent.

[0078] From the viewpoint of ensuring durability and ensuring a contact area with the conductive structure on the side, the thickness of the first adhesive layer is 5 to 100 μm, preferably 5 to 50 μm, and more preferably 10 to 35 μm.

[0079] In addition, from the viewpoint of antistatic function and touch sensor sensitivity, the surface resistance value of the first adhesive layer is 1.0×10 10 ~1.0×10 12 Ω / □, preferably 1.0×10 10 ~8.0×10 11 Ω / □, more preferably 2.0×10 10 ~6.0×10 11 It should be noted that by adjusting the surface resistance value of the first adhesive layer to the above range, the amount of the antistatic agent used in the adhesive layer can be suppressed, and the turbidity caused by the amount of the antistatic agent in the adhesive layer and the decrease in adhesion with the adhesion layer can be suppressed, which is a preferred embodiment.

[0080] In the embedded liquid crystal panel of the present invention, the variation ratio (b / a) of the surface resistance value on the side of the first adhesive layer is 5 or less. Wherein, the above-mentioned a represents the surface resistance value of the first adhesive layer side when the above-mentioned separator is peeled off immediately after the first polarizing film with an adhesive layer is prepared in a state where the above-mentioned first adhesive layer is provided on the above-mentioned first polarizing film and a separator is provided on the above-mentioned first adhesive layer; the above-mentioned b represents the surface resistance value of the first adhesive layer side when the above-mentioned separator is peeled off after the above-mentioned first polarizing film with an adhesive layer is placed in a humidified environment of 60°C×95%RH for 120 hours and further dried at 40°C for 1 hour. When the above-mentioned variation ratio (b / a) is greater than 5, the antistatic function of the layer composed of the adhesive layer and the adhesion-promoting layer in a humidified environment will be reduced. The above-mentioned variation ratio (b / a) is 5 or less, preferably 4.5 or less, more preferably 4 or less, further preferably 0.4 to 3.5, and most preferably 0.4 to 2.5.

[0081] The surface resistance value of the first adhesive layer side in the above-mentioned adhesive layer-attached polarizing film is preferably controlled to 2.0×10 8 ~1.0×10 11Ω / □, and to satisfy the antistatic function of the initial value (room temperature condition: 23°C×65%RH) and after humidification (for example, after 120 hours at 60°C×95%RH), and the sensitivity of the touch sensor will not be reduced, and the durability in a humidified or heated environment will not be reduced. The above surface resistance value can be adjusted by controlling the surface resistance values ​​of the above adhesion layer and the first adhesive layer (monomer) respectively. The above surface resistance value is more preferably 6.0×10 8 ~8.0×10 10 Ω / □, more preferably 8.0×10 8 ~6.0×10 10 Ω / □.

[0082] As the adhesive forming the first adhesive layer, various adhesives can be used, for example: rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives, cellulose adhesives, etc. can be listed. The adhesive base polymer can be selected according to the type of the above-mentioned adhesive. Among the above-mentioned adhesives, acrylic adhesives can be preferably used from the viewpoints of excellent optical transparency, showing suitable adhesive properties of wettability, cohesion and adhesion, and excellent weather resistance, heat resistance, etc.

[0083] The acrylic adhesive comprises a (meth) acrylic polymer as a base polymer. The (meth) acrylic polymer generally contains an alkyl (meth) acrylate as a monomer unit as a main component. It should be noted that (meth) acrylate refers to acrylate and / or methacrylate, and the (meth) of the present invention also has the same meaning.

[0084] As the (meth)acrylic acid alkyl ester constituting the main skeleton of the (meth)acrylic polymer, there can be exemplified a linear or branched (meth)acrylic acid alkyl ester having an alkyl carbon number of 1 to 18. These (meth)acrylic acid alkyl esters can be used alone or in combination. The average carbon number of these alkyl groups is preferably 3 to 9.

[0085] In addition, from the viewpoints of adhesive properties, durability, adjustment of phase difference, adjustment of refractive index, etc., an aromatic ring-containing alkyl (meth)acrylate such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate may be used as a comonomer.

[0086] In order to improve adhesiveness and heat resistance, one or more comonomers having a polymerizable functional group containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group may be introduced into the (meth)acrylic polymer by copolymerization. Specific examples of such copolymerizable monomers include: hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-hydroxymethylcyclohexyl methacrylate; carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethylacryloyl phosphate, and the like.

[0087] In addition, examples of the monomers for modification include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide and other (N-substituted)amide monomers; (meth)acrylic acid alkylaminoalkyl ester monomers such as (meth)aminoethyl acrylate, N,N-dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; (meth)acrylic acid alkoxyalkyl ester monomers such as (meth)methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; N-(meth)acryloyloxy Succinimide monomers such as methylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide, and N-acryloyl morpholine; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-dodecylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-dodecylitaconimide.

[0088] In addition, as the modifying monomer (comonomer), vinyl acetate, vinyl propionate, N-vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl Vinyl monomers such as oxazole, vinyl morpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinyl caprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate; polyethylene glycol (meth)acrylate, polypropylene (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, etc.; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl acrylate, etc. In addition, isoprene, butadiene, isobutylene, vinyl ether, etc. can be cited.

[0089] In addition, as copolymerizable monomers (comonomers) other than the above, silane monomers containing silicon atoms can be listed. As silane monomers, for example: 3-acryloxypropyl triethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, 4-vinyl butyl trimethoxysilane, 4-vinyl butyl triethoxysilane, 8-vinyl octyl trimethoxysilane, 8-vinyl octyl triethoxysilane, 10-methacryloxy decyl trimethoxysilane, 10-acryloxy decyl trimethoxysilane, 10-methacryloxy decyl triethoxysilane, 10-acryloxy decyl triethoxysilane, etc. can be listed.

[0090] In addition, as the comonomer, a polyfunctional monomer having two or more unsaturated double bonds such as (meth)acrylic acid or vinyl groups, such as esters of (meth)acrylic acid and polyols such as tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, and the like in which two or more unsaturated double bonds such as (meth)acryloyl groups or vinyl groups are added to the skeleton of polyester, epoxy, urethane, and the like as the same functional groups as the monomer components can be used.

[0091] The (meth)acrylic polymer preferably contains alkyl (meth)acrylate as the main component in a weight ratio of all constituent monomers, and the ratio is preferably 60 to 90% by weight, more preferably 65 to 88% by weight, and further preferably 70 to 85% by weight. It is preferred that alkyl (meth)acrylate is used as the main component because it has excellent adhesive properties.

[0092] In the (meth)acrylic polymer, the weight ratio of the comonomer in all the constituent monomers is preferably 10 to 40% by weight, more preferably 12 to 35% by weight, and even more preferably 15 to 30% by weight.

[0093] Among these comonomers, from the viewpoint of adhesion and durability, hydroxyl-containing monomers and carboxyl-containing monomers are preferably used. Hydroxyl-containing monomers and carboxyl-containing monomers can be used in combination. When the adhesive composition contains a crosslinking agent, these comonomers become reaction points with the crosslinking agent. Since the reactivity of hydroxyl-containing monomers, carboxyl-containing monomers, etc. with intermolecular crosslinking agents is sufficient, it is preferably used to improve the cohesion and heat resistance of the obtained adhesive layer. From the viewpoint of reoperability, hydroxyl-containing monomers are preferably used. In addition, from the viewpoint of taking into account durability and reoperability, carboxyl-containing monomers are preferably used.

[0094] When the comonomer contains a hydroxyl group-containing monomer, the ratio is preferably 0.01 to 15% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight. When the comonomer contains a carboxyl group-containing monomer, the ratio is preferably 0.01 to 10% by weight, more preferably 0.1 to 5% by weight, and even more preferably 0.2 to 1% by weight.

[0095] Generally, the weight average molecular weight of the (meth) acrylic polymer of the present invention is preferably 1 million to 2.5 million. Considering durability, especially heat resistance, the weight average molecular weight is preferably 1.2 million to 2 million. When the weight average molecular weight is 1 million or more, it is preferred in terms of heat resistance. In addition, when the weight average molecular weight is greater than 2.5 million, there is a tendency for the adhesive to harden easily and it becomes easy to peel off. In addition, the weight average molecular weight (Mw) / number average molecular weight (Mn) representing the molecular weight distribution is preferably 1.8 to 10, more preferably 1.8 to 7, and more preferably 1.8 to 5. When the molecular weight distribution (Mw / Mn) is greater than 10, it is not preferred in terms of durability. It should be noted that the weight average molecular weight and the molecular weight distribution (Mw / Mn) can be determined by GPC (gel permeation chromatography) and the values ​​calculated by polystyrene conversion.

[0096] Such (meth)acrylic polymers can be produced by appropriately selecting known production methods such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymers may be any copolymers such as random copolymers, block copolymers, graft copolymers, etc.

[0097] <Antistatic Agent>

[0098] Examples of the antistatic agent used for forming the first adhesive layer include materials that can impart antistatic properties, such as ionic compounds, ionic surfactants, conductive polymers, and conductive fine particles. Among them, ionic compounds are preferred from the perspective of compatibility with the base polymer and transparency of the adhesive layer.

[0099] Examples of the ionic surfactant include cationic surfactants (e.g., quaternary ammonium salts, onium salt type, sulfonium salt type, etc.), anionic type (carboxylic acid type, sulfonate type, sulfate type, phosphate type, phosphite type, etc.), zwitterionic type (sulfobetaine type, alkyl betaine type, alkyl imidazole type Various surfactants can be used, such as betaine type) or non-ionic type (polyol derivatives, β-cyclodextrin inclusion compound, sorbitan fatty acid monoester / diester, polyoxyalkylene derivatives, amine oxide, etc.).

[0100] Examples of the conductive polymer include polymers such as polyaniline, polythiophene, polypyrrole, and polyquinoxaline. Among them, polyaniline and polythiophene are preferably used. Polythiophene is particularly preferred.

[0101] As conductive particles, metal oxides such as tin oxide, antimony oxide, indium oxide, and zinc oxide can be cited. Among them, tin oxide is preferred. As conductive particles of tin oxide, for example, in addition to tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide composite, titanium oxide-tin oxide composite, etc. can be cited. The average particle size of the particles is about 1 to 100 nm, preferably 2 to 50 nm.

[0102] In addition, examples of antistatic agents other than the above include: acetylene black, Ketjen black, natural graphite, artificial graphite, titanium black, homopolymers of monomers having ion conductive groups of cationic (quaternary ammonium salts, etc.), zwitterionic (betaine compounds, etc.), anionic (sulfonates, etc.) or nonionic (glycerol, etc.) types, or copolymers of the above monomers with other monomers, polymers having a portion derived from acrylate or methacrylate containing a quaternary ammonium salt group, and other ion conductive polymers; permanent antistatic agents of the type obtained by alloying hydrophilic polymers such as polyethylene methacrylate copolymers with acrylic resins, etc.

[0103] In addition, as ionic compounds, inorganic cation anion salts and / or organic cation anion salts can be preferably used, and in particular, inorganic cation anion salts are used as preferred embodiments. Compared with organic cation anion salts, ionic compounds containing inorganic cations (inorganic cation anion salts) can suppress the reduction of the adhesion (anchoring force) between the adhesion layer and the adhesive layer when used, and are therefore more preferred. It should be noted that the so-called "inorganic cation anion salt" in the present invention generally refers to an alkali metal salt formed by an alkali metal cation and an anion, and the alkali metal salt can use an organic salt and an inorganic salt of an alkali metal. In addition, the so-called "organic cation anion salt" in the present invention refers to an organic salt, the cation part of which is composed of an organic substance, and the anion part can be an organic substance or an inorganic substance. "Organic cation anion salt" is also referred to as an ionic liquid and an ionic solid. In addition, as an anion component constituting an ionic compound, from the aspect of antistatic function, preferably a fluorine-containing anion is used.

[0104] <Alkali Metal Salt>

[0105] Examples of the alkali metal ions constituting the cation portion of the alkali metal salt include ions of lithium, sodium, potassium, etc. Among these alkali metal ions, lithium ions are preferred.

[0106] The anion part of the alkali metal salt may be composed of an organic substance or an inorganic substance. Examples of the anion part constituting the organic salt include: CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - PF6 - 、CO3 2- , the following general formulas (1) to (4), and (FSO2)2N - Indicates anions, etc.

[0107] (1): (C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10),

[0108] (2): CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10),

[0109] (3): - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10),

[0110] (4): (C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (wherein p and q are integers from 1 to 10).

[0111] In particular, the anion part containing fluorine atoms is preferably used because it can obtain an ionic compound with good ionization. As the anion part constituting the inorganic salt, Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - Among the anions containing fluorine atoms, fluorine-containing imide anions are preferred, among which bis(trifluoromethanesulfonyl)imide anions and bis(fluorosulfonyl)imide anions are preferred. In particular, bis(fluorosulfonyl)imide anions can impart excellent antistatic properties with a relatively small amount of addition, maintain adhesive properties, and are beneficial to durability in a humidified or heated environment, and are therefore preferred.

[0112] As the organic salt of the alkali metal, specific examples include sodium acetate, sodium alginate, sodium lignin sulfonate, sodium toluene sulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, LiO3S(CF2)3SO3K, etc. Among them, L iCF3SO3, Li(FSO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, etc., more preferably Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N and other fluorinated imide lithium salts, particularly preferably lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide.

[0113] In addition, examples of inorganic salts of alkali metals include lithium perchlorate and lithium iodide.

[0114] <Organic cation anion salt>

[0115] The organic cation anion salt used in the present invention is composed of a cation component and an anion component, wherein the cation component is composed of an organic substance. Specific examples of the cation component include: pyridine Cation, piperidine Cation, pyrrolidine Cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazole Cation, Tetrahydropyrimidine Cation, dihydropyrimidine Cation, pyrazole Cationic, pyrazoline Cations, tetraalkylammonium cations, trialkylsulfonium cations, tetraalkyl Cations, etc.

[0116] Examples of the anion component include Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , the following general formulas (1) to (4), and (FSO2)2N - Indicates anions, etc.

[0117] (1): (C n F 2n+1 SO2)2N- (where n is an integer from 1 to 10),

[0118] (2): CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10),

[0119] (3): - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10),

[0120] (4): (C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (wherein p and q are integers of 1 to 10). Among them, in particular, since anions containing fluorine atoms (fluorine-containing anions) can obtain ionic compounds with good ionization properties, they are preferably used. Among the anions containing fluorine atoms, fluorine-containing imide anions are preferred, among which bis(trifluoromethanesulfonyl)imide anions and bis(fluorosulfonyl)imide anions are preferred. In particular, bis(fluorosulfonyl)imide anions can impart excellent antistatic properties with a relatively small amount of addition, maintain adhesive properties, and are beneficial to durability in humidified and heated environments, so they are preferred.

[0121] In addition, as ionic compounds, in addition to the above-mentioned inorganic cation anion salts (alkali metal salts) and organic cation anion salts, inorganic salts such as ammonium chloride, aluminum chloride, cupric chloride, ferrous chloride, ferric chloride, and ammonium sulfate can be listed. These ionic compounds can be used alone or in combination of two or more.

[0122] The amounts of the adhesive and antistatic agent used vary depending on their types, but can be controlled so that the surface resistance value of the first adhesive layer obtained is 1.0×10 10 ~1.0×10 12Ω / □. For example, relative to 100 parts by weight of the base polymer of the adhesive (for example, a (meth) acrylic polymer), it is preferred to use an antistatic agent in the range of 0.05 to 8 parts by weight (for example, in the case of an ionic compound). When the antistatic agent is used within the above range, it is preferred in terms of improving the antistatic performance. On the other hand, when it exceeds 8 parts by weight, when the adhesive layer or the embedded liquid crystal panel containing the above adhesive layer is exposed to humidification conditions, there is sometimes a hidden danger of precipitation / segregation of the antistatic agent and turbidity of the adhesive layer, so it is not preferred. In addition, there is also a hidden danger of reduced adhesion (anchoring force) between the adhesion layer and the adhesive layer, and sometimes foaming / peeling occurs in a humidified or heated environment, and the durability becomes insufficient, so it is not preferred. In addition, the antistatic agent is preferably 0.1 parts by weight or more, and more preferably 0.2 parts by weight or more. In terms of satisfying durability, it is preferably used at 6 parts by weight or less, and more preferably 4 parts by weight or less.

[0123] In addition, the adhesive composition forming the first adhesive layer may contain a crosslinking agent corresponding to the base polymer. As the base polymer, for example, when a (meth) acrylic polymer is used, as the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate may be used. As the organic crosslinking agent, isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, etc. may be cited. Polyfunctional metal chelates are chelates formed by covalent bonding or coordination bonding of polyvalent metals and organic compounds. As polyvalent metal atoms, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. may be cited. As atoms in covalently bonded or coordinately bonded organic compounds, oxygen atoms, etc. may be cited, and as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. may be cited.

[0124] The amount of the crosslinking agent used is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, more preferably 0.02 to 2 parts by weight, and even more preferably 0.03 to 1 part by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0125] In addition, the adhesive composition forming the first adhesive layer can contain silane coupling agents and other additives. For example, polyether compounds such as polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet light absorbers, inhibitors, inorganic or organic fillers, metal powders, granular, foil-like objects, etc. can be appropriately added according to the use purpose. In addition, the redox type of adding a reducing agent can also be adopted within the controllable range. Relative to 100 weight parts of (methyl) acrylic polymers, these additives are preferably used in the range of less than 5 weight parts, more preferably less than 3 weight parts, and further preferably less than 1 weight part.

[0126] <Adhesion-promoting layer>

[0127] The above-mentioned adhesion promoting layer constituting the in-cell liquid crystal panel of the present invention is characterized by containing a conductive polymer, having a thickness of 0.01 to 0.5 μm and a surface resistance of 1.0×10 8 ~1.0×10 10 Ω / □.

[0128] From the viewpoint of the stability of the surface resistance value, the adhesion with the adhesive layer, and the stability of the antistatic function by ensuring the contact area with the conductive structure, the thickness of the above-mentioned anchor layer is 0.01 to 0.5 μm, preferably 0.01 to 0.4 μm, and more preferably 0.02 to 0.3 μm.

[0129] In addition, from the viewpoint of antistatic function and the sensitivity of the touch sensor, the surface resistance value of the above-mentioned adhesion layer is 1.0×10 8 ~1.0×10 10 Ω / □, preferably 1.0×10 8 ~8.0×10 9 Ω / □, more preferably 2.0×10 8 ~6.0×10 9 Ω / □. In particular, since the above-mentioned adhesion-enhancing layer has conductivity (antistatic property), compared with the case where the antistatic property is imparted by a separate adhesive layer, the antistatic function is excellent, and the amount of the antistatic agent used in the above-mentioned adhesive layer can be suppressed to a small amount. From the perspective of the precipitation / segregation of the antistatic agent, the poor appearance such as white turbidity in a humidified environment, and durability, it is a preferred method. In addition, in the case where a conductive structure is provided on the side of the first polarizing film with an adhesive layer constituting the embedded liquid crystal panel, since the adhesion-enhancing layer has conductivity, it is possible to ensure the contact area with the conductive structure as an antistatic layer (conductive layer), and the antistatic function is excellent, compared with the case where the antistatic property is imparted only by the adhesive layer, and therefore it is preferred.

[0130] From the perspective of optical properties, appearance, antistatic effect and the stability of the antistatic effect when heated and humidified, it is preferred to use the above-mentioned conductive polymer. It is particularly preferred to use conductive polymers such as polyaniline and polythiophene. Conductive polymers can appropriately use organic solvent-soluble, water-soluble, and water-dispersible polymers, and preferably use water-soluble conductive polymers or water-dispersible conductive polymers. This is because water-soluble conductive polymers and water-dispersible conductive polymers can be prepared in the form of aqueous solutions or aqueous dispersions to form a coating liquid for forming an antistatic layer, and the above-mentioned coating liquid does not need to use non-aqueous organic solvents, which can suppress the denaturation of the optical film substrate caused by the above-mentioned organic solvents. It should be noted that the aqueous solution or aqueous dispersion can contain an aqueous solvent other than water. For example, alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol can be listed.

[0131] In addition, the water-soluble conductive polymers or water-dispersible conductive polymers such as polyaniline and polythiophene preferably have hydrophilic functional groups in the molecule. As the hydrophilic functional group, for example, sulfonic acid group, amino group, amide group, imine group, quaternary ammonium salt group, hydroxyl group, sulfhydryl group, hydrazine group, carboxyl group, sulfate group, phosphate group or their salts can be listed. By having a hydrophilic functional group in the molecule, it is easy to dissolve in water and easy to be dispersed in water in a particulate form, and the water-soluble conductive polymer or water-dispersible conductive polymer can be easily prepared. It should be noted that when using polythiophene polymers, polystyrene sulfonic acid is usually used in combination.

[0132] Examples of commercially available water-soluble conductive polymers include polyaniline sulfonic acid (manufactured by Mitsubishi Rayon Co., Ltd., weight average molecular weight converted to polystyrene is 150,000), etc. Examples of commercially available water-dispersible conductive polymers include polythiophene conductive polymers (manufactured by Nagase ChemteX, trade name: Denatron series), etc.

[0133] In addition, as a material for forming the adhesion layer, in order to improve the film forming property of the conductive polymer and the adhesion to the optical film, etc., a binder component may be added together with the conductive polymer. In the case where the conductive polymer is a water-soluble conductive polymer or a water-dispersible conductive polymer, a water-soluble or water-dispersible binder component is used. Examples of the binder include: Oxazoline polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinyl pyrrolidone, polystyrene resins, polyethylene glycol, pentaerythritol, etc. Polyurethane resins, polyester resins, and acrylic resins are particularly preferred. These adhesives can be used alone or in combination of two or more in their intended use.

[0134] The amount of the conductive polymer and the binder used varies depending on their types, and the surface resistance of the obtained adhesion layer is preferably controlled to 1.0×10 8 ~1.0×10 10 Ω / □.

[0135] <Surface treatment layer>

[0136] The surface treatment layer may be provided on the side of the first polarizing film where the adhesion promoting layer is not provided. The surface treatment layer may be provided on the transparent protective film used for the first polarizing film, or may be provided separately from the transparent protective film. As the surface treatment layer, a hard coating layer, an anti-glare treatment layer, an anti-reflection layer, an anti-adhesion layer, etc. may be provided.

[0137] As the surface treatment layer, a hard coating is preferred. As the material for forming the hard coating, for example, a thermoplastic resin or a material cured by heat or radiation can be used. As the above-mentioned material, radiation curing resins such as thermosetting resins, ultraviolet curing resins, and electron beam curing resins can be cited. Among them, ultraviolet curing resins that can efficiently form a cured resin layer by simple processing operations in the curing treatment using ultraviolet irradiation are preferred. As these curing resins, various resins such as polyesters, acrylics, urethanes, amides, silicones, epoxies, and melamines can be cited, including their monomers, oligomers, polymers, etc. From the viewpoint of fast processing speed and less damage to the substrate caused by heat, radiation curing resins are particularly preferred, and ultraviolet curing resins are particularly preferred. The ultraviolet curing resins preferably used can include, for example, resins having ultraviolet polymerizable functional groups, including monomers and oligomer components of acrylics having 2 or more, especially 3 to 6 of the above functional groups. In addition, a photopolymerization initiator can be added to the ultraviolet curing resin.

[0138] In addition, as the above-mentioned surface treatment layer, an anti-glare treatment layer and an anti-reflection layer for improving visibility can be provided. In addition, an anti-glare treatment layer and an anti-reflection layer can be provided on the above-mentioned hard coating layer. The constituent material of the anti-glare treatment layer is not particularly limited, for example, radiation curing resin, thermosetting resin, thermoplastic resin, etc. can be used. As the anti-reflection layer, titanium oxide, zirconium oxide, silicon oxide, magnesium fluoride, etc. can be used. The anti-reflection layer can be provided with multiple layers. In addition, as the surface treatment layer, an anti-adhesion layer, etc. can be cited.

[0139] The surface treatment layer may be provided with conductivity by containing an antistatic agent. As the antistatic agent, the antistatic agents exemplified above may be used.

[0140] <Other layers>

[0141] In addition to the above-mentioned layers, the pressure-sensitive adhesive layer-attached polarizing film of the present invention may further include an easily adhesive layer on the surface of the first polarizing film on which the anchor layer is provided, or may be subjected to various easily adhesive treatments such as corona treatment and plasma treatment.

[0142] <In-cell liquid crystal unit and in-cell liquid crystal panel>

[0143] Hereinafter, the in-cell liquid crystal unit B and the in-cell liquid crystal panel C will be described.

[0144] (In-cell liquid crystal unit B)

[0145] like Figure 2 to Figure 6 As shown, the embedded liquid crystal unit B includes a liquid crystal layer 20, a first transparent substrate 41 and a second transparent substrate 42 sandwiching the liquid crystal layer 20 on both sides, and the liquid crystal layer 20 includes liquid crystal molecules that are uniformly oriented in the absence of an electric field. In addition, a touch sensing electrode portion related to the functions of the touch sensor and touch drive is provided between the first transparent substrate 41 and the second transparent substrate 42.

[0146] like Figure 2 , Figure 3 , Figure 6 As shown, the touch sensing electrode portion can be formed by touch sensor electrodes 31 and touch drive electrodes 32. The touch sensor electrodes referred to here refer to touch detection (receiving) electrodes. The touch sensor electrodes 31 and touch drive electrodes 32 can be independently formed by various patterns. For example, when the embedded liquid crystal unit B is a plane, it can be configured in a pattern in which they are independently set in the X-axis direction and the Y-axis direction to cross at right angles. In addition, Figure 2 , Figure 3 , Figure 6 In the figure, the touch sensor electrode 31 is arranged on the side closer to the first transparent substrate 41 (visible side) than the touch drive electrode 32, but contrary to the above, the touch drive electrode 32 can also be arranged on the side closer to the first transparent substrate 41 (visible side) than the touch sensor electrode 31.

[0147] On the other hand, Figure 4 , Figure 5 As shown, the touch sensing electrode unit may use an electrode 33 in which a touch sensor electrode and a touch driving electrode are integrated.

[0148] In addition, the touch sensor electrode portion may be disposed between the liquid crystal layer 20 and the first transparent substrate 41 or between the liquid crystal layer 20 and the second transparent substrate 42 . Figure 2 , Figure 4 This is a case where the touch sensor electrode portion is disposed between the liquid crystal layer 20 and the first transparent substrate 41 (closer to the visible side than the liquid crystal layer 20 ). Figure 3 , Figure 5 This is a case where the touch sensor electrode portion is disposed between the liquid crystal layer 20 and the second transparent substrate 42 (closer to the backlight side than the liquid crystal layer 20 ).

[0149] In addition, if Figure 6 As shown, the touch sensing electrode unit may include a touch sensor electrode 31 between the liquid crystal layer 20 and the first transparent substrate 41 , and a touch driving electrode 32 between the liquid crystal layer 20 and the second transparent substrate 42 .

[0150] It should be noted that the driving electrode in the touch sensing electrode portion (the electrode 33 formed by integrating the touch driving electrode 32 , the touch sensor electrode, and the touch driving electrode) may also be used as a common electrode for controlling the liquid crystal layer 20 .

[0151] As the liquid crystal layer 20 used in the embedded liquid crystal unit B, a liquid crystal layer containing liquid crystal molecules uniformly oriented in the absence of an electric field can be used. As the liquid crystal layer 20, for example, an IPS type liquid crystal layer can be preferably used. In addition, as the liquid crystal layer 20, for example, any type of liquid crystal layer such as TN type, STN type, π type, VA type, etc. can be used. The thickness of the above-mentioned liquid crystal layer 20 is, for example, about 1.5μm to 4μm.

[0152] As described above, the embedded liquid crystal unit B has a touch sensor electrode portion related to the touch sensor and touch drive functions in the liquid crystal unit, and does not have a touch sensor electrode outside the liquid crystal unit. That is, no conductive layer (surface resistance value of 1×10 13 Ω / □ or less). It should be noted that Figure 2 to Figure 6 The in-cell type liquid crystal panel C described in shows the order of the respective structures, but the in-cell type liquid crystal panel C may have other structures as appropriate. A color filter substrate may be provided on the liquid crystal cell (the first transparent substrate 41).

[0153] The material forming the transparent substrate may include, for example, glass or a polymer film. Examples of the polymer film include, for example, polyethylene terephthalate, polycycloolefin, polycarbonate, etc. When the transparent substrate is formed of glass, its thickness may be, for example, about 0.1 mm to 1 mm. When the transparent substrate is formed of a polymer film, its thickness may be, for example, about 10 μm to 200 μm. The transparent substrate may have an easy-adhesion layer or a hard coating layer on its surface.

[0154] The touch sensor electrode 31 (capacitive sensor), the touch drive electrode 32, or the electrode 33 formed by integrating the touch sensor electrode and the touch drive electrode, which forms the touch sensing electrode part, is formed in the form of a transparent conductive layer. As the constituent material of the above-mentioned transparent conductive layer, there is no particular limitation, and examples thereof include: metals such as gold, silver, copper, platinum, palladium, aluminum, nickel, chromium, titanium, iron, cobalt, tin, magnesium, tungsten, and alloys of these metals. In addition, as the constituent material of the above-mentioned transparent conductive layer, metal oxides of indium, tin, zinc, gallium, antimony, zirconium, and cadmium can be listed, and specifically metal oxides composed of indium oxide, tin oxide, titanium oxide, cadmium oxide, and mixtures thereof can be listed. In addition, other metal compounds composed of copper iodide and the like can be used. As needed, the above-mentioned metal oxide can also further contain oxides of metal atoms shown in the above-mentioned group. For example, indium oxide (ITO) containing tin oxide, tin oxide containing antimony, etc. can be preferably used, and ITO is particularly preferably used. As ITO, it is preferred to contain 80 to 99% by weight of indium oxide and 1 to 20% by weight of tin oxide.

[0155] The electrodes in the above-mentioned touch sensing electrode portion (touch sensor electrodes 31, touch drive electrodes 32, electrodes 33 formed by integrating the touch sensor electrodes and the touch drive electrodes) can usually be formed in the form of a transparent electrode pattern on the inner side of the first transparent substrate 41 and / or the second transparent substrate 42 (on the liquid crystal layer 20 side in the embedded liquid crystal unit B) by a common method. The above-mentioned transparent electrode pattern is usually electrically connected to a lead wire (not shown) formed at the end of the transparent substrate, and the above-mentioned lead wire is connected to a controller IC (not shown). In addition to a comb shape, the shape of the transparent electrode pattern can be any shape such as a stripe shape, a diamond shape, etc. according to the application. The height of the transparent electrode pattern is, for example, 10nm to 100nm, and the width is 0.1mm to 5mm.

[0156] (In-cell LCD panel C)

[0157] like Figures 2 to 6As shown, the embedded liquid crystal panel C of the present invention has a polarizing film A with an adhesive layer on the visible side of the embedded liquid crystal unit B, and a second polarizing film 11 on the opposite side. The above-mentioned polarizing film A with an adhesive layer is arranged on the first transparent substrate 41 side of the above-mentioned embedded liquid crystal unit B through the above-mentioned first adhesive layer 2, and no conductive layer is sandwiched between them. On the other hand, the second polarizing film 11 is arranged on the second transparent substrate 42 side of the above-mentioned embedded liquid crystal unit B through the second adhesive layer 12. The first polarizing film 1 and the second polarizing film 11 in the above-mentioned polarizing film A with an adhesive layer are arranged on both sides of the liquid crystal layer 20 in a manner such that the transmission axes (or absorption axes) of their respective polarizers are orthogonal.

[0158] As the second polarizing film 11, the polarizing film described in the first polarizing film 1 can be used. As the second polarizing film 11, the same polarizing film as the first polarizing film 1 can be used, or a different polarizing film can be used.

[0159] The adhesive described in the first adhesive layer 2 can be used to form the second adhesive layer 12. As the adhesive used to form the second adhesive layer 12, the same adhesive as the first adhesive layer 2 can be used, or a different adhesive can be used. The thickness of the second adhesive layer 12 is not particularly limited, and is, for example, about 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.

[0160] In addition, in the embedded liquid crystal panel C, a conductive structure 50 may be provided on the side of the above-mentioned adhesion-promoting layer 3 and the first adhesive layer 2 of the above-mentioned polarizing film A with an adhesive layer. The conductive structure 50 may be provided on the entire side of the above-mentioned adhesion-promoting layer 3 and the first adhesive layer 2, or may be provided on a portion of the side. When the above-mentioned conductive structure is provided on a portion of the side, in order to ensure the conduction of the side, the above-mentioned conductive structure is preferably provided at a ratio of 1% by area or more, more preferably 3% by area or more of the area of ​​the above-mentioned side. It should be noted that, in addition to the above, Figure 2 As shown, a conductive material 51 may be provided on the side surface of the first polarizing film 1 .

[0161] By using the conductive structure 50, the generation of static electricity can be suppressed by connecting the potential from the side of the above-mentioned adhesion layer 3 and the first adhesive layer 2 to other appropriate positions. As materials for forming the conductive structures 50 and 51, conductive pastes such as silver, gold or other metal pastes can be listed. In addition, conductive adhesives and any other suitable conductive materials can be used. The conductive structure 50 can also be formed into a linear shape extending from the side of the above-mentioned adhesion layer 3 and the first adhesive layer 2. For the conductive structure 51, the same linear shape can also be formed.

[0162] In addition, the first polarizing film 1 disposed on the visible side of the liquid crystal layer 20 and the second polarizing film 11 disposed on the opposite side of the visible side of the liquid crystal layer 20 can be used by stacking other optical films according to the adaptability of their respective configuration positions. As the above-mentioned other optical films, for example, reflective plates, semi-transmissive plates, phase difference films (including wavelength plates of 1 / 2, 1 / 4, etc.), viewing angle compensation films, brightness improvement films, etc. are sometimes used in the formation of liquid crystal display devices, etc. These can be used in one layer or two or more layers.

[0163] (Liquid Crystal Display Device)

[0164] The liquid crystal display device (touch sensor function built-in liquid crystal display device) using the in-cell liquid crystal panel of the present invention can be suitably used to form a component of a liquid crystal display device such as a device using a backlight or a reflector in a lighting system.

[0165] Example

[0166] Hereinafter, the present invention will be specifically described by manufacturing examples and embodiments, but the present invention is not limited to these embodiments. It should be noted that the parts and % in each example are weight basis. The following "initial value" (room temperature placement condition) refers to the value of the state placed at 23°C × 65%RH, and "after humidification" refers to the value measured after being placed in a humidified environment of 60°C × 95%RH for 120 hours and further dried at 40°C for 1 hour.

[0167] <Measurement of Weight Average Molecular Weight of (Meth)Acrylic Polymer>

[0168] The weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by GPC (gel permeation chromatography). The molecular weight distribution (Mw / Mn) was also measured in the same manner.

[0169] ·Analysis device: Made by Tosoh Corporation, HLC-8120GPC

[0170] ·Chromatographic column: G7000H manufactured by Tosoh Corporation XL +GMH XL +GMH XL

[0171] Column size: each Total 90cm

[0172] Column temperature: 40℃

[0173] Flow rate: 0.8mL / min

[0174] Injection volume: 100μL

[0175] ·Eluent: Tetrahydrofuran

[0176] Detector: Differential Refractometer (RI)

[0177] Standard sample: polystyrene

[0178] (Preparation of polarizing film)

[0179] A polyvinyl alcohol film with a thickness of 80 μm was dyed in a 0.3% iodine solution at 30°C for 1 minute between rollers with different speed ratios, and stretched to 3 times. Then, it was immersed in an aqueous solution containing 4% boric acid and 10% potassium iodide at 60°C for 0.5 minutes, and stretched to a total stretching ratio of 6 times. Next, it was immersed in an aqueous solution containing 1.5% potassium iodide at 30°C for 10 seconds, washed, and then dried at 50°C for 4 minutes to obtain a polarizer with a thickness of 30 μm. A saponified triacetyl cellulose (TAC) film with a thickness of 25 μm was bonded to one side of the polarizer, and a corona-treated cycloolefin polymer (COP) film with a thickness of 13 μm was bonded to the other side using ultraviolet-curing acrylic adhesives, respectively, to produce a polarizing film.

[0180] The anchor layer-formed surface side (cycloolefin polymer (COP) film side) of the polarizing film was subjected to a corona treatment (0.1 kW, 3 m / min, 300 mm width) as an adhesion-facilitating treatment.

[0181] (Preparation of Materials for Forming Adhesion-Promoting Layer)

[0182] 8.6 parts of a solution containing 30 to 90% by weight of a urethane polymer and 10 to 50% by weight of a thiophene polymer (trade name: Denatron P-580W, manufactured by Nagase ChemteX Co., Ltd.) and 10.6 parts of a solution containing A coating liquid for forming an anchor layer having a solid content of 0.5 wt% was prepared by mixing 1 part of a solution of 10 to 70 wt% of an oxazoline acrylic polymer and 10 to 70 wt% of a polyoxyethylene-containing methacrylate (trade name: EPOCROS WS-700, manufactured by Nippon Catalyst Co., Ltd.) with 90.4 parts of water.

[0183] (Formation of adhesion-promoting layer)

[0184] The anchor layer-forming coating liquid was applied to one side (corona-treated side) of the polarizing film to a thickness shown in Table 1 after drying, and dried at 80° C. for 2 minutes to form an anchor layer.

[0185] (Preparation of acrylic polymer 1)

[0186] A monomer mixture containing 73.3 parts of butyl acrylate (BA), 21 parts of phenoxyethyl acrylate (PEA), 5 parts of N-vinyl pyrrolidone (NVP), 0.3 parts of acrylic acid (AA), and 0.4 parts of 4-hydroxybutyl acrylate (HBA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator and 100 parts of ethyl acetate were added to 100 parts of the above monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. Then, the liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of acrylic polymer 1 having a weight average molecular weight (Mw) of 1.6 million and Mw / Mn=3.8.

[0187] (Preparation of acrylic polymer 2)

[0188] A monomer mixture containing 77 parts of butyl acrylate (BA), 20 parts of phenoxyethyl acrylate (PEA), and 3 parts of 4-hydroxybutyl acrylate (HBA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator and 100 parts of ethyl acetate were added to 100 parts of the above monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. Then, the liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of acrylic polymer 2 having a weight average molecular weight (Mw) of 1.7 million and Mw / Mn=3.4.

[0189] (Preparation of Adhesive Composition)

[0190] To 100 parts of the solid content of the acrylic polymer solution obtained above, an ionic compound was blended according to the amounts (solid content, active ingredient) shown in Table 1, and further 0.1 parts of an isocyanate crosslinking agent (Takenate D160N, manufactured by Mitsui Chemicals, Inc., trimethylolpropane hexamethylene diisocyanate), 0.3 parts of benzoyl peroxide (NYPER BMT, manufactured by NOF Corporation), and 0.2 parts of γ-glycidoxypropylmethoxysilane (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) were blended to prepare solutions of acrylic adhesive compositions used in the examples and comparative examples.

[0191] The abbreviations of the ionic compounds described in Table 1 are as follows.

[0192] Li-TFSI: Lithium bis(trifluoromethanesulfonyl)imide, manufactured by Mitsubishi Chemical Materials Corporation, alkali metal salt

[0193] TBMA-TFSI: tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, manufactured by Mitsubishi Materials Corporation, ionic liquid (organic cation anion salt)

[0194] EMI-FSI: 1-ethyl-3-methylimidazole Bis(fluorosulfonyl)imide salt, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., ionic liquid (organic cation anion salt)

[0195] (Formation of Adhesive Layer)

[0196] Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate (PET) film (separator: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with a silicone release agent and dried at 155° C. for 1 minute so that the thickness of the adhesive layer after drying was the thickness shown in Table 1, thereby forming an adhesive layer on the surface of the separator. The adhesive layer was transferred to a polarizing film having an adhesion promoter layer formed thereon.

[0197] <Examples 1 to 6, Comparative Examples 1 to 5, and Reference Example 1>

[0198] On one side (corona-treated side) of the polarizing film obtained above, an anchor layer and a pressure-sensitive adhesive layer were formed in this order using the combinations shown in Table 1 to produce a pressure-sensitive adhesive layer-attached polarizing film.

[0199] In addition, in Comparative Example 6, the ionic compound was not blended in the preparation of the adhesive composition.

[0200] The anchor layer, the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer-attached polarizing film obtained in the above-mentioned Examples and Comparative Examples were evaluated as follows.

[0201] <Anchor strength (adhesion)>

[0202] The polarizing film with adhesive layer obtained in the examples and comparative examples was cut into 25 mm wide x 50 mm long. The adhesive layer surface was bonded to the vapor-deposited surface of the vapor-deposited film on the surface of a 50 μm thick polyethylene terephthalate film, so that they were in contact. Then, the end of the polyethylene terephthalate film was peeled off by hand to confirm that the adhesive layer was attached to one side of the polyethylene terephthalate film, and then a tensile tester (Autograph AG-1 manufactured by Shimadzu Corporation) was used to measure the anchoring force (adhesion) (N / 25mm) between the polarizing film and the adhesive layer, or between the tackifier layer and the adhesive layer, under the conditions of 180° peeling and a tensile speed of 300 mm / min at room temperature (25°C).

[0203] As the above-mentioned anchoring force, it is preferably 10 N / 25 mm or more, more preferably 15 N / 25 mm or more, and still more preferably 18 N / 25 mm or more. When the anchoring force is less than 10 N / 25 mm, the sealing property is weak, and when treating the polarizing film with the adhesive layer, the following adverse conditions may occur and become problems: paste defects and paste contamination occur at the end, or peeling occurs in terms of durability, or peeling occurs when the liquid crystal display device falls, etc.

[0204] <Surface resistance value (Ω / □): Conductivity>

[0205] (i) For the surface resistance value of the tackifier layer, the surface of the tackifier layer side of the polarizing film with the tackifier layer before forming the adhesive layer was measured (refer to Table 1).

[0206] (ii) For the surface resistance value of the adhesive layer, the surface of the adhesive layer formed on the separator was measured (refer to Table 1).

[0207] (iii) For the surface resistance value on the adhesive layer side, the surface resistance value of the adhesive layer surface was measured after peeling the separator from the obtained polarizing film with the adhesive layer (refer to Table 2).

[0208] The measurement was carried out using MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd. (i) is the value measured after applying a voltage of 10 V for 10 seconds, and (ii) and (iii) are the values measured after applying a voltage of 250 V for 10 seconds.

[0209] It should be noted that the change ratio (b / a) in Table 2 is a value calculated from the surface resistance value (a) of "initial value" and the surface resistance value (b) of "after humidification" (rounded to two decimal places).

[0210] In addition, as an index with less risk of reduction in antistatic function and reduction in touch sensor sensitivity, a smaller change ratio value is preferred. In this regard, the following criteria were used for evaluation. It should be noted that the evaluation result with practical problems is ×.

[0211] (Evaluation criteria)

[0212] ◎: The change ratio is greater than 0.3 and 2 or less.

[0213] ○: The change ratio is greater than 0.1 and 0.3 or less, or greater than 2 and 5 or less.

[0214] ×: The change ratio is 0.1 or less, or greater than 5.

[0215] <ESD test>

[0216] In Examples 1 to 6 and Comparative Examples 1 to 6, after peeling the separator from the polarizing film with an adhesive layer, as Figure 3 shown, it was attached to the visible side of the in-cell liquid crystal cell.

[0217] Next, a silver paste with a width of 5 mm was applied to the side faces of the attached polarizing film so as to cover the side faces of the polarizing film, the tackifier layer, and the adhesive layer, and it was connected to a ground electrode from the outside.

[0218] In Reference Example 1, after peeling the separator from the polarizing film with an adhesive layer, it was attached to the visible side (sensor layer) of the out-cell liquid crystal cell.

[0219] The above liquid crystal display panel was mounted on a backlight device, and an electrostatic discharge gun was applied to the polarizing film surface on the visible side at a voltage of 12 kV, and the time until the white spot due to electricity disappeared was measured, and this was used as the "initial value" and judged according to the following criteria. In addition, for "after humidification", it was also judged according to the following criteria in the same manner as the "initial value". It should be noted that the evaluation result with problems in practical use is ×.

[0220] (Evaluation Criteria)

[0221] ◎: Within 3 seconds.

[0222] ○: Greater than 3 seconds and within 10 seconds.

[0223] ×: Greater than 10 seconds.

[0224] <TSP Sensitivity>

[0225] In Examples 1 to 6 and Comparative Examples 1 to 6, the lead wiring (not shown) near the transparent electrode pattern inside the in-cell liquid crystal cell was connected to a controller IC (not shown). In Reference Example 1, the lead wiring near the transparent electrode pattern on the visible side of the out-cell liquid crystal cell was connected to a controller IC, and a liquid crystal display device with a built-in touch sensing function was fabricated. With the input display device using the liquid crystal display device with a built-in touch sensing function in the operating state, visual inspection was carried out to confirm whether there was any malfunction.

[0226] ○: No malfunction.

[0227] ×: There is a malfunction.

[0228] <Humidification Cloudiness Test>

[0229] The polarizing film with adhesive layer obtained in the examples and comparative examples was cut into a size of 50 mm × 50 mm. After the diaphragm was peeled off, the surface of the adhesive layer was bonded to an alkali glass (manufactured by Matsunami Glass Co., Ltd., with a thickness of 1.1 mm), and then subjected to an autoclave treatment at 50°C and 5 atm for 15 minutes to serve as a measurement sample for the turbidity test. After the above-mentioned measurement sample was placed in an environment of 60°C × 95% RH for 120 hours, it was taken out at room temperature and the haze value was measured 10 minutes later. It should be noted that the haze value was measured using a haze meter HM150 manufactured by Murakami Color Technology Research Institute Co., Ltd.

[0230] (Evaluation Criteria)

[0231] ○: Haze is 10 or less, which is a level that does not cause any practical problems

[0232] ×: Haze is greater than 10, which is a level that is problematic in practical use.

[0233] [Table 1]

[0234]

[0235] [Table 2]

[0236]

[0237] According to the evaluation results of Tables 1 and 2 above, it can be confirmed that in all embodiments, the adhesion, antistatic properties, suppression of static unevenness, touch sensor sensitivity, and humidification turbidity prevention are excellent. On the other hand, in the comparative example, the surface resistance values ​​of the adhesion layer and the adhesive layer are not within the given range, and therefore, the results that can satisfy all the evaluations cannot be obtained. In particular, it is confirmed that: in Comparative Example 5, the thickness of the adhesion layer is thick, and a surface resistance value lower than the given range is obtained, and a malfunction caused by abnormal sensitivity of the touch sensor occurs. In Comparative Example 6, since an antistatic agent is not added to the adhesive layer, static unevenness occurs, and it takes time for the white spots to disappear due to poor conduction. It should be noted that in Reference Example 1, it was confirmed that the sensitivity of the touch sensor is reduced when applied to an external embedded liquid crystal unit.

Claims

1. A polarizing film with an adhesive layer, comprising an adhesive layer and a polarizing film, in, The polarizing film with an adhesive layer comprises the polarizing film, an adhesion-promoting layer, and the adhesive layer in this order. The adhesion-promoting layer contains a conductive polymer, and the adhesive layer contains an antistatic agent. The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □, The thickness of the adhesive layer is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, and The variation ratio (b / a) of the surface resistance value on the adhesive layer side is 5 or less, In the variation ratio (b / a), a represents the surface resistance value of the adhesive layer side when the separator is peeled off immediately after the polarizing film with an adhesive layer is produced in which the adhesive layer is provided on the polarizing film and a separator is provided on the adhesive layer; b represents the surface resistance value of the pressure-sensitive adhesive layer side when the pressure-sensitive adhesive layer-attached polarizing film was placed in a humidified environment of 60° C.×95% RH for 120 hours and further dried at 40° C. for 1 hour and then the separator was peeled off.

2. The polarizing film with an adhesive layer according to claim 1, wherein The antistatic agent is an ionic compound having an inorganic cation.

3. The polarizing film with an adhesive layer according to claim 2, wherein The ionic compound contains a fluorine-containing anion.

4. A polarizing film with an adhesive layer for an in-cell liquid crystal panel, which is used for an in-cell liquid crystal panel having an in-cell liquid crystal cell, wherein the in-cell liquid crystal cell has: A liquid crystal layer including liquid crystal molecules uniformly aligned in the absence of an electric field, A first transparent substrate and a second transparent substrate sandwiching the liquid crystal layer on both sides, and A touch sensing electrode portion related to the touch sensor and touch driving functions between the first transparent substrate and the second transparent substrate, in, The polarizing film with an adhesive layer is arranged on the visible side of the in-cell liquid crystal cell. The adhesive layer of the polarizing film with an adhesive layer is arranged between the polarizing film of the polarizing film with an adhesive layer and the in-cell liquid crystal cell. The polarizing film with an adhesive layer comprises the polarizing film, an adhesion-promoting layer, and the adhesive layer in this order. The adhesion-promoting layer contains a conductive polymer, and the adhesive layer contains an antistatic agent. The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □, The thickness of the adhesive layer is 5 to 100 μm, and the surface resistance is 1.0×10 10 ~1.0×10 12 Ω / □, and The variation ratio (b / a) of the surface resistance value on the adhesive layer side is 5 or less, In the variation ratio (b / a), a represents the surface resistance value of the adhesive layer side when the separator is peeled off immediately after the polarizing film with an adhesive layer is produced in which the adhesive layer is provided on the polarizing film and a separator is provided on the adhesive layer; b represents the surface resistance value of the pressure-sensitive adhesive layer side when the pressure-sensitive adhesive layer-attached polarizing film was placed in a humidified environment of 60° C.×95% RH for 120 hours and further dried at 40° C. for 1 hour and then the separator was peeled off.

5. The polarizing film with an adhesive layer for an in-cell type liquid crystal panel according to claim 4, wherein The antistatic agent is an ionic compound having an inorganic cation.

6. The polarizing film with an adhesive layer for an in-cell type liquid crystal panel according to claim 5, wherein The ionic compound contains a fluorine-containing anion.

7. An in-cell liquid crystal panel, comprising: In-cell liquid crystal unit, A first polarizing film disposed on the visible side of the in-cell liquid crystal unit and a second polarizing film disposed on the side opposite to the visible side, and a first adhesive layer disposed between the first polarizing film and the embedded liquid crystal cell, The in-cell liquid crystal unit has: A liquid crystal layer including liquid crystal molecules uniformly aligned in the absence of an electric field, A first transparent substrate and a second transparent substrate sandwiching the liquid crystal layer on both sides, and A touch sensing electrode portion related to the touch sensor and touch driving functions between the first transparent substrate and the second transparent substrate, in, The polarizing film with an adhesive layer comprises the first polarizing film, an adhesion-promoting layer, and the first adhesive layer in this order. The adhesion-promoting layer contains a conductive polymer, and the first adhesive layer contains an antistatic agent. The thickness of the adhesion-promoting layer is 0.01 to 0.5 μm, and the surface resistance is 1.0×10 8 ~1.0×10 10 Ω / □, the thickness of the first adhesive layer is 5 to 100 μm, and the surface resistance value is 1.0×10 10 ~1.0×10 12 Ω / □, Furthermore, the variation ratio (b / a) of the surface resistance value on the first adhesive layer side is 5 or less, In the variation ratio (b / a), The a represents the surface resistance value of the first adhesive layer side when the separator is peeled off immediately after the first polarizing film with an adhesive layer is produced in which the first adhesive layer is provided on the first polarizing film and a separator is provided on the first adhesive layer; b represents the surface resistance value of the first pressure-sensitive adhesive layer side when the separator is peeled off after the pressure-sensitive adhesive layer-attached first polarizing film is placed in a humidified environment of 60° C.×95% RH for 120 hours and further dried at 40° C. for 1 hour.

8. The in-cell liquid crystal panel according to claim 7, wherein: The antistatic agent is an ionic compound having an inorganic cation.

9. The in-cell liquid crystal panel according to claim 8, wherein: The ionic compound contains a fluorine-containing anion. 10 . A liquid crystal display device comprising the in-cell liquid crystal panel according to claim 7 .

Citation Information

Patent Citations

  • Input display device

    JP2013105154A